Interaction of Lipase with Lipid Model Systems - Zaitsev, Sergei Yu.; Zaitsev, Ilia S.; Milaeva, Irina V. (Journal of Research Updates in Polymer Science, 2020)
The aim of this work was to study the interaction of lipases (as an important biopolymer) with models of biomembranes based on the phospholipid and cholesterol. Lipases (triacylglycerolacyl hydrolases) are widely distributed enzymes and well-known by their hydrolytic activity. The study of the lipase interactions with lipid vesicles in aqueous dispersions is of fundamental and practical interest. The pure phosphatidylcholine from egg yolk (ePC) and cholesterol (Chol) were obtained from Sigma-Aldrich. Lipase was obtained from hog pancreas. Measurements of the current and equilibrium surface tension (ST and eST) values were carried out using a BPA-1P device and ADSA program. The particle sizes in the prepared colloidal solutions were determined by the method of dynamic light scattering. An addition of lipase led to some decrease both, of ST and eST for the samples of ePC:Chol (in the ratios from19:1 to 1:1). The mean particle diameter (MPD) and effective particle diameter (EPD) values for the samples of ePC:Chol changed drastically by lipase addition. The EPD/MPD ratios increased from 1.7 to 2.0, from 1.8 to 2.6, from 2.3 to 6.5, from 1.5 to 2.9 for the samples of ePC:Chol at the ratios of 19:1, 14:1, 9:1, 7:1, respectively by lipase concentration increase. This general tendency can be explained by strong interaction of lipase with lipid membrane that leads to the formation of the mixed particles ePC:Chol:lipase with more narrow particle size distribution as compared to the initial EPD/MPD ratio (for the ePC:Chol mixture without lipase).